Diagnosis of freemartinism in heifers born co-twin to a bull - Larson, B.L.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The wide variance in anatomical characteristics among heifers born co-twin to a bull make diagnosis of freemartinism by measurements of vaginal length or the distance between the anus and vulva unreliable. Change in serum luteinizing hormone (LH) in response to injection of estrogen or gonadotropin releasing hormone (GnRH) is different in freemartins compared to normal heifers but is also an unreliable predictor of freemartinism. Presently, the most conclusive way to establish freemartinism in a heifer born co-twin to a bull is to measure the percentage of XX and XY chromosomes in cells from whole blood, which is a specialized and expensive procedure.
Keywords: Beef; Freemartin; Twins; XY chromosome; Chimer